LOW RCS DIPOLE ARRAY SYNTHESIS BASED ON MOM-PSO HYBRID ALGORITHM - Wang, Wen-Tao; Gong, Shu-Xi; Zhang, Yu-Jie; Zha, Feng-Tao; Ling, Jin; Wan, Tingting (Electromagnetic waves (Cambridge, Mass.), 2009)
In this paper, a hybrid algorithm combined method of moments (MoM) with particle swarm optimization (PSO) is used to realize low radar cross section (RCS) array synthesis. Both the scattering factor and the radiation factor are involved in the proposed objective function to achieve the promising dipole array with a reduced RCS and satisfied radiation performance. To improve the optimization efficiency, radiation constraint conditions are adopted to avoid unnecessary scattering calculation. The symmetric matrix and block treatment are also used to fill the MoM impedance matrix. The optimization results show that the proposed algorithm is able to achieve RCS reduction of 5.5 dB for dipole array.